An Updated Panorama of “Living Low-Training High” Altitude/Hypoxic Methods - Girard, Olivier; Brocherie, Franck; Goods, Paul S. R.; Millet, Gregoire P. (Frontiers in Sports and Active Living, 2020)
With limited costs and travel constraints for athletes, the “living low-training high” (LLTH) approach is becoming an important intervention for modern sport. The popularity of the LLTH model of altitude training is also associated with the fact that it only causes a slight disturbance to athletes’ usual daily routine, allowing them to remain in their home environment and maintain their regular lifestyle. In this perspective article, we discuss the evolving boundaries of the LLTH paradigm and its practical applications for athletes. Passive modalities include intermittent hypoxic exposure at rest (IHE) and Ischemic preconditioning (IPC). Active modalities use either local [blood flow restricted (BFR) exercise] and/or systemic hypoxia [continuous low-intensity training in hypoxia (CHT), interval hypoxic training (IHT), repeated-sprint training in hypoxia (RSH), sprint interval training in hypoxia (SIH) and resistance training in hypoxia (RTH)]. A combination of hypoxic methods targeting different attributes also represents an attractive solution. In conclusion, the scope of LLTH altitude training methods is now wider than in the past as it includes the application of systemic and local hypoxia stimuli, or a combination of both, for performance enhancement in many disciplines.